2002
DOI: 10.1097/00006534-200202000-00032
|View full text |Cite
|
Sign up to set email alerts
|

A 1-Year Study of Osteoinduction in Hydroxyapatite-Derived Biomaterials in an Adult Sheep Model: Part I

Abstract: The study presented here investigated hydroxyapatite biomaterials implanted in soft-tissue sites in adult sheep to determine whether these materials are osteoinductive and whether the rate of osteoinduction can be increased by manipulating the composition and porosity of the implants. For the study, 16.8-mm x 5-mm discs were prepared from mixtures of hydroxyapatite and beta-tricalcium phosphate. Five mixtures of hydroxyapatite-ceramic and hydroxyapatite-cement paste forms were studied: 100 percent hydroxyapati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
151
2
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(162 citation statements)
references
References 39 publications
5
151
2
4
Order By: Relevance
“…This finding matches observations from previous studies in which it was suggested that the microstructure was responsible for the osteoinductive potential of biomaterials. 2,11,23,24 Although the exact mechanism of this process is still unknown, the fact remains that in this model BCP1150 somehow stimulated undifferentiated cells to generate bone at its surface. BCP1300 completely lacked this ability.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This finding matches observations from previous studies in which it was suggested that the microstructure was responsible for the osteoinductive potential of biomaterials. 2,11,23,24 Although the exact mechanism of this process is still unknown, the fact remains that in this model BCP1150 somehow stimulated undifferentiated cells to generate bone at its surface. BCP1300 completely lacked this ability.…”
Section: Discussionmentioning
confidence: 96%
“…Osteoinduction has been shown in soft tissues of various animal models by a number of calcium-phosphate (CaP) containing bulk ceramics such as hydroxyapatite (HA), 2-9 a-tricalcium phosphate (a-TCP), b-TCP-, BCP, a-pyrophosphate, and b-pyrophosphate. 2,3,6,10 -18 Furthermore, ectopic bone formation has been observed by octacalcium phosphate (OCP)-coated porous biomaterials, 12,13,19 CaP cements, 11,20 and glass ceramics. 21 Osteoinduction has also been reported by porous alumina ceramic 22 and titanium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomaterials have a range of properties, from osteoinductive and osteoconductive to immunomodulatory. Hydroxyapatite and calcium phosphate as well as their composites such as HA/poly(DL-lactic-co-glycolic acid) (PLGA), in the form of ceramics, cements and coatings have shown osteoinduction in animal models [60][61][62][63][64][65][66]. Various hybrid materials combined as co-polymers, polymer blends and polymer-ceramic blends have also shown efficacy [67][68][69][70][71][72][73].…”
Section: Biomaterialsmentioning
confidence: 99%
“…14 The biological response of the host tissue to this type of material may vary according to its porosity, shape and size of particles, as well as their compositional characteristics, such as the amount of HA and βT C P. [15][16][17][18] HA-βTCP ceramics have been reported as biocompatible, osteoconductive and osteoinductive. The latter is due to being capable of differentiating mesenchymal stem cells into osteoblasts and chondroblasts.…”
Section: Introductionmentioning
confidence: 99%